Knockdown of YAP/TAZ Inhibits the Migration and Invasion of Fibroblast Synovial Cells in Rheumatoid Arthritis by Regulating Autophagy - Wei Zhou; Qin Shen; Hui Wang; Jie Yang; Chen Zhang; Zijing Deng; Keyan Wu; Yang Zhou; Jing Zeng; Yu Zhang; Weigan Shen (Journal of Immunology Research)
The purpose of this study was to investigate the effect of knockdown of the yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) on the migration and invasion of the rheumatoid arthritis fibroblast-like synoviocytes (RA-FLS) and to preliminarily elucidate the mechanisms between YAP/TAZ and autophagy in the migration and invasion of RA-FLS. RA-FLS stable knockdown of YAP or TAZ was successfully established by using lentiviral-mediated gene knockdown techniques. Wound healing assay and Transwell assay were used to evaluate the effect of knockdown of YAP or TAZ on the migration and invasion of RA-FLS. Reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) and western blotting assays were performed to examine the expression of indicated genes. The results showed that YAP and TAZ were upregulated in RA-FLS, and knockdown of YAP or TAZ inhibited the migration and invasion, reduced the expression of N-cadherin and Vimentin, and increased the accumulation of E-cadherin and β-catenin in RA-FLS. Our results also demonstrated that knockdown of YAP or TAZ promoted autophagy which increased the accumulation of LC3B-II and ULK1 and decreased the amount of SQSTM1/p62 in RA-FLS. Furthermore, our data displayed that inhibition of autophagy either with 3-MA or CQ can partially reverse the decrease of migration and invasion induced by YAP and TAZ knockdown in RA-FLS. Our experiments preliminarily revealed that YAP/TAZ and autophagy play important roles in the migration and invasion of RA-FLS, which might provide novel targets for the treatment of RA.